Peran Guru Dalam Menanamkan Nilai-Nilai Pendidikan Islam Bagi Anak Berkebutuhan Khusus di SLB ABC Melati Aisyiyah Deli Serdang - Lathifa Shufi; Nurussakianah Daulay; Sapri Sapri (Dinasti Review, 2024)
This research aims to identify the role of teachers, analyze factors supporters and obstacles as well as solutions in instilling Islamic education values for children with special needs at SLB ABC Melati Aisyiyah Deli Serdang. This research was conducted using a qualitative field research approach. Research instruments through observation, interviews and document study. The data sources for this research are primary and secondary data sources obtained from SLB ABC Melati Aisyiyah Deli Serdang. The results of the research show that instilling Islamic education values for children with special needs at SLB ABC Melati Aisyiyah Deli Serdang is carried out by instilling aqidah values, shari'ah (worship) values, and moral values at the SMPLB and SMALB levels with special needs for deaf and deaf people mentally disabled. For the deaf, both at SMPLB and SMALB levels, the cultivation of the Aqidah includes material on the pillars of faith, giving the understanding that Allah is One and only Allah must be worshipped, reciting the Koran. The cultivation of Sharia (worship) includes getting used to noon prayers in congregation, giving alms, fasting, learning to become a priest, participating in religious activities carried out every month by the school. Moral cultivation includes being kind to colleagues, polite, courteous and respectful towards teachers/ parents, honest, disciplined, and responsible. For the type of mental retardation at both SMPLB and SMALB levels, the cultivation of faith includes the pillars of faith, memorizing prayers, reciting the Koran. cultivating shari'ah (worship) includes congregational noon prayers, learning the call to prayer and iqamah. The cultivation of morals includes respect for elders, politeness and courtesy towards teachers/parents, honesty. The methods and strategies used are lectures, demonstrations, stories, habituation, example, targhib and tarhib. Supporting factors are the principal, teachers, parents, environment, private tutoring. Inhibiting factors are inadequate facilities and infrastructure, communication barriers, absence of RPP. Solutions to improve facilities and infrastructure, improve communication patterns, create lesson plans.